ANALISIS DETERMINAN VOLUME EKSPOR BATUBARA INDONESIA KE LIMA NEGARA TUJUAN EKSPOR - Annisa Ashari Rahma (2023)
Indonesia is in the third place in the world's largest coal producing country and plus, Indonesia is relied on in terms of the world's largest coal exporter. Currently, coal still dominates in the use of power plants. Even though the switch from fossil energy to renewable energy has been misused by many countries, this switch will reduce the use of fossil energy so that this can affect fluctuations in the volume of coal exports. In addition, there are other economic variables that affect fluctuations in coal export volume. In this study, several economic variables are used, including inflation, GDP and exchange rates. In this case, the research is aimed at analyzing the determinants that affect fluctuations in the volume of coal exports in Indonesia in receipt countries, namely India, China, Japan, South Korea and Malaysia in 2005 - 2021. The number of observers in this study is 85 data, where the data used is of secondary obtained through the official website of the world bank and the Central Bureau of Statistics. The data analysis technique used in this study is the panel data regression method and the fixed effect model as the selected model. The results of this study indicate that (1) Inflation has no significant effect on the volume of Indonesian coal exports to recipient countries. (2) GDP has a significant positive effect on the volume of Indonesian coal exports in recipient countries. (3) The exchange rate has a significant negative effect on the volume of Indonesian coal exports in receiving countries and (4) renewable energy has a significant negative effect on the volume of Indonesian coal exports in receiving countries.